Sampling from skewed population the sampling design of the 2011 survey of enterprises in the Philippines. - Barrios, Erniel B. (Philippine Statistician, 2012)
The sampling design for the 2011 Survey of Enterprises in the Philippines is used to illustrate sampling from a skewed population that is characterized by large population variance. The modified Lavallee-Hidiroglu stratification algorithm is used to simultaneously determine the stratum boundaries and the optimum sample size that will minimize the coefficient of variation. The principles behind "threshold" sampling is then used in excluding segment of the population containing "minimal" information while the segment containing the "most" information is considered as certainty ratum. An estimation procedure is also presented.